2014
DOI: 10.1111/jth.12461
|View full text |Cite
|
Sign up to set email alerts
|

Risk assessment of venous thrombosis in families with known hereditary thrombophilia: the MARseilles‐NImes prediction model

Abstract: Summary. Background: Although predicting the risk of venous thrombosis (VT) in an individual from a family with inherited thrombophilia is of major importance, it is often not feasible. Objectives: To develop a simple risk assessment model that improves prediction of the risk of VT for individuals of families with inherited thrombophilia. Patients/methods: 1201 relatives from 430 families with inherited thrombophilia (deficiencies of antithrombin, protein C or protein S, and the factor V Leiden and F2 20210A m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 29 publications
0
16
0
Order By: Relevance
“…However, recent literature has emphasized the high prevalence of VTE in this patient population. In fact, one study reported that the rate of VTE in patients with SCD was close to that observed in those with hereditary thrombophilias [37]. In another study, upon evaluation of over 1.5 million SCD admissions between 1979 and 2003, it was found that these patients had a risk of PE approximately 3.5 times higher than their African American controls [38].…”
Section: Venous Thromboembolism and Pulmonary Embolismmentioning
confidence: 93%
“…However, recent literature has emphasized the high prevalence of VTE in this patient population. In fact, one study reported that the rate of VTE in patients with SCD was close to that observed in those with hereditary thrombophilias [37]. In another study, upon evaluation of over 1.5 million SCD admissions between 1979 and 2003, it was found that these patients had a risk of PE approximately 3.5 times higher than their African American controls [38].…”
Section: Venous Thromboembolism and Pulmonary Embolismmentioning
confidence: 93%
“…For primary prevention of VTE, several risk prediction models applicable to asymptomatic carriers of hereditary thrombophilia have been derived from case-control studies. [109][110][111] The number of genetic markers in these models varies greatly and can include more than 30 SNPs. 110 Some scores combine genetic elements with other risk factors such as age and family history of VTE.…”
Section: Areas For Advancementmentioning
confidence: 99%
“…It is associated with the presence of polymorphic variants of two coagulation factors: FV R506Q, better known as factor Leiden, and prothrombin (PT) G20210A [6]. Furthermore, although its role in thrombosis development is indirect and more complex, polymorphism of gene encoding for methylenetetrahydrofolate reductase (MTHFR C677T), the enzyme engaged in homocysteine metabolism, is also involved [7][8][9].…”
Section: Introductionmentioning
confidence: 99%